"I wouldn't really believe statistics" – Challenges with influenza vaccine acceptance among healthcare workers in Singapore. Issue 15 (5th April 2018) - Sundaram, Neisha; Duckett, Kathryn; Yung, Chee Fu; Thoon, Koh Cheng; Sidharta, Sucitro; Venkatachalam, Indumathi; Chow, Angela; Yoong, Joanne
Abstract: Background: Influenza vaccine acceptance among healthcare workers (HCWs) is a worldwide problem, but relatively little research has focussed on Asia, including Singapore. Despite widespread access and recommendations from public health authorities, influenza vaccine uptake remains suboptimal among HCWs. Methods: Our qualitative study used focus group discussions to identify and explain factors limiting influenza vaccine acceptance among HCWs in Singapore. A total of 73 doctors, nurses, allied health and ancillary staff across three public hospitals were included. Results: Challenges identified include a fear of contracting influenza from vaccination exacerbated by negative anecdotes regarding vaccine safety and efficacy, distrust of published efficacy data, uncertainty regarding relevance of existing data for Singapore, reluctance to introduce chemicals or overmedicate, pain from injection, low risk attributed to influenza and limited awareness of influenza transmission with a preference for alternatives in patient protection. Differences in attitudes were observed across vocational groups. Lack of overt promotion by hospital leadership in some institutions, perceived vaccine hesitancy among doctors, access, and work culture that implicitly encourages working through illness were further barriers. Conclusion: Our findings highlight a combination of misperceptions about influenza vaccination and cognitive biases at the individual level, and challenges at the institutional level limiting uptake. Findings indicate an urgent need to provide targeted education and communication. Rather than providing more data, we recommend a widely-disseminated, locally-compiled synthesis addressing specific concerns of hesitant HCWs. Tailoring interventions to specific vocational groups should be considered. Institutional norms and culture may have a powerful influence in setting default behaviours: more effort is needed in improving influenza vaccine promotion and priority at some institutions, integrating vaccine-related communication with other infection control communication and addressing influenza vaccine hesitancy among doctors as a priority. Finally, further study of strategies to address cognitive biases affecting influenza vaccine acceptance in Singapore is desirable.